Valoración social del manejo de Mauritia flexuosa L. aguaje en relación con aspectos ambientales y socioeconómicos en la comunidad de Nueva York río Tigre Loreto 2025 - Lache Reategui, Jhoan Jordan (2025)
This quantitative, non-experimental, cross-sectional, correlational study analyzes the social assessment of aguaje (Mauritia flexuosa L.) management in relation to environmental and socioeconomic aspects in the NUEVA YORK community, Tigre River, Loreto, 2025. The study involved a purposive sample of 20 adult residents involved in extractive activities. Data collection was conducted using a 33-item structured questionnaire with a reliability of 0.815 (Cronbach's alpha). The analysis employed the Shapiro-Wilk test and, due to the sample size, Spearman's correlation coefficient. The results show that there is a strong cultural and economic appreciation for aguaje, which is an important source of income. However, technical limitations persist in its management, such as the limited use of sustainable methods. A positive environmental impact—such as the regeneration of aguajales—is recognized, although there are weaknesses in community governance. The community shows a willingness to participate in more sustainable management, although technical knowledge is still low. A positive and significant relationship was found between social appreciation and socioeconomic effects, but not with environmental effects, suggesting that ecological awareness is not fully incorporated into the appreciation of the resource. The need to strengthen organizational, educational, and regulatory capacities for comprehensive and sustainable aguaje management is highlighted.